Design of portable shell tube heat exchanger for solar powered water distiller - Khiabani, Aydin (2011)
Based on the United Nation records, around 20% of world populations suffer lack of potable water and a third of the Earth’s population live in the water stressed area such as Sahara in Africa and South East Asia. Therefore, the importance of solar powered water distillation systems, especially portable devices seems necessary. The current portable solar distillers are designed based on effective evaporation or distillation method and are usually used for distilling salt water or a liquid phased material. Moreover, they are able to produce 4 liters in eight hours which is far too slow for anyone to wait. On the other hand, larger size water distillers should be installed for more amounts of produced water and they not only are not portable, but also very huge and usually very heavy for carrying and installing in every place. For enhancing of high condensation and evaporation efficiency, various methods mostly involve conventional heat transfer. Moreover the devices which are composed of a glass heat exchanger, served as a condenser for vapor condensing were produced in black paint solar absorber. There is a tank for supply water and a tank for storage of produced distilled water. In this study, a portable shell and tube condenser for solar powered water distiller which is for army personnel or camping groups to enter ecotourism Islands or jungle trekking and preparing their necessity fresh water at hand. This Portable design with considering some performance parameters such as: limited length (L<1m), light weight (W<10kg) and higher efficiency (>40 L/day) has been designed by using of mathematical module, validating and rating of the results via experimental test and implicit numerical analysis. Rating results showed that accumulated mass water significantly depended on the inlet vapor temperature and volume, heat exchanger material, coolant water temperature and volume. Thus, Stainless Steel 304 and Pyrex glass in the same thermo dynamical condition (vapor temperature, vapor volume, coolant temperature and coolant volume) are considered as preliminary supposition for material in mathematical module. Finally, because of small amounts of vapor in this device,different quality of vapor has negligible effect on physical and mechanical performance of portable shell and tube condensers. These inexpensive shell and tube heat exchangers permitted to produce 40 liter/day distilled water from vapor with 378K inlet temperature in atmosphere pressure. If inlet pressure increase, vapor temperature will decline and thereupon, heat exchanger's efficiency tangibility will be increased.